2007
DOI: 10.2169/internalmedicine.46.6342
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Pulmonary Hypertension and Its Clinical Relevance in Patients with Interstitial Pneumonias: Comparison between Idiopathic and Collagen Vascular Disease Associated Interstitial Pneumonias

Abstract: Object This study was undertaken to investigate the frequency of pulmonary hypertension (PH), and clinical parameters associated with PH in patients with idiopathic interstitial pneumonias (IIPs) and collagen vascular disease-associated interstitial pneumonias (CVD-IPs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…In general, the prevalence of PH was similar in studies from Europe [18,25,[40][41][42][43][44][45][47][48][49], North America [5,6,26,28,46,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67], Asia and Africa [37,[68][69][70][71][72][73][74][75], although the majority of evidence was reported from North America (n=23, 53%). Across studies, the prevalence of PH among IPF patients ranged from 3% to 86%; most estimates tended to be between 30% and 50% (figure 3) [25, 43, 44, 47, 50, 52-66, 68, 71-73].…”
Section: Pulmonary Hypertensionmentioning
confidence: 84%
“…In general, the prevalence of PH was similar in studies from Europe [18,25,[40][41][42][43][44][45][47][48][49], North America [5,6,26,28,46,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67], Asia and Africa [37,[68][69][70][71][72][73][74][75], although the majority of evidence was reported from North America (n=23, 53%). Across studies, the prevalence of PH among IPF patients ranged from 3% to 86%; most estimates tended to be between 30% and 50% (figure 3) [25, 43, 44, 47, 50, 52-66, 68, 71-73].…”
Section: Pulmonary Hypertensionmentioning
confidence: 84%
“…Data on the prevalence and clinical features of PH in idiopathic NSIP are sparse and basically unknown; in this setting, the level of PH is usually mild-tomoderate [49]. In an echocardiographic study, HANDA et al [50] reported the incidence of PH to be 28% among 70 patients with idiopathic interstitial pneumonia, 11 of which had NSIP. The mean systolic PAP in this group was 30.2 mmHg.…”
Section: Other Ilds Associated With Phmentioning
confidence: 99%
“…Consequently, the diagnosis of PH may be missed in ILD patients until signs of right heart failure develop [4,[20][21][22][23][24][25]. Moreover, specific and effective treatment for pulmonary arterial hypertension (PAH) has become available only recently and the previous lack of therapeutic options has also certainly abrogated the necessity of identifying ILD patients with associated PH.…”
mentioning
confidence: 99%